2022
DOI: 10.3390/molecules27196227
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Mirificin and Other Bioactive Isoflavone Glycosides from the Kudzu Root Lyophilisate Using Centrifugal Partition and Flash Chromatographic Techniques

Abstract: Pueraria lobata (Willd.) Ohwi is a legume taxon native to Southeast Asia and widely used in traditional medicine systems of that region. The therapeutic applications of the underground parts of this species (known as kudzu root) are related to its high content of isoflavones, mainly the characteristic C-glycoside derivatives. Within this group, the most explored compound both phytochemically and pharmacologically is puerarin. However, current scientific findings document important anti-biodegenerative effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In addition, the peak area data from the granule fingerprint showed that the peak area of puerarin and mirificin was the largest among all the peak areas, indicating their remarkable significance in terms of quality control. A few studies have shown that calycosin is a component of Astragali Radix, and puerarin and mirificin are important components of Pueraria Lobata 25,32 . These findings underscore the necessity for stringent quality control measures for fried Astragali Radix and Pueraria Lobata to ensure the stability of ZTF granules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the peak area data from the granule fingerprint showed that the peak area of puerarin and mirificin was the largest among all the peak areas, indicating their remarkable significance in terms of quality control. A few studies have shown that calycosin is a component of Astragali Radix, and puerarin and mirificin are important components of Pueraria Lobata 25,32 . These findings underscore the necessity for stringent quality control measures for fried Astragali Radix and Pueraria Lobata to ensure the stability of ZTF granules.…”
Section: Resultsmentioning
confidence: 99%
“…31 Components with VIP values greater than 1 played a crucial role in of Pueraria Lobata. 25,32 These findings underscore the necessity for stringent quality control measures for fried Astragali Radix and Pueraria Lobata to ensure the stability of ZTF granules.…”
Section: Opls-damentioning
confidence: 94%
See 1 more Smart Citation
“…Ohwi. by combined centrifugal partition (CPC) and FC methods [ 171 ]. The current advancements include fully automated flash chromatography equipment equipped with robotic fraction collectors and online detection units, significantly enhancing the efficiency of separating, isolating, and purifying constituent compounds within a complex mixture of crude extract and identification [ 172 ].…”
Section: Approaches and Techniques For The Biodiscovery Of Anti-infla...mentioning
confidence: 99%
“…Kudzu root (Pueraria lobate (Willd.) Ohwi, KR), a legume taxon indigenous to Southeast Asia, boasts a rich variety of species and can be found across China [ 1 ], including in Hebei, Guangxi, Anhui, Liaoning, and Shandong. In fact, it has become one of the most prevalent twining shrub plants in urban forests.…”
Section: Introductionmentioning
confidence: 99%